A study on road safety awareness and practices among secondary school’s students - Lay, Hui Lian (2018)
Road traffic accident is defined as one of the significant public health problems around the world. Nowadays, Road traffic accidents are increasing in Malaysia especially among the young people between 13 to 19 years old. Simple measures such as awareness and practice of road safety measures could effectively reduce the impact of road traffic accidents on the people’s lives. This research was conducted in order to evaluate the knowledge level of secondary school’s students toward road safety measure, to determine the level of road safety awareness and practices among secondary school’s students, and to compare the road safety awareness between male secondary school’s students and female secondary school’s students. The cross sectional study was done among 210 secondary school’s students. The data collected was carried out at Sekolah Menengah Kebangsaan Bandar Kuala Krai by distributing the questionnaires to the secondary school’s students. The data obtained was analyzed quantitatively by using Statistical Packages Social Sciences (SPSS) version 24 and presented with the aid of frequency distributions, pie charts, and tables. Based on the result findings, majority of secondary school’s students had high level of knowledge, awareness and practices about road safety. However, the female secondary school’s students had higher road safety knowledge, awareness and practices than male secondary school’s students. Periodic organization of road safety program at school and the roles of parents in educating their children were essential for effectively increasing the level of knowledge, awareness and practices toward road safety